1966
DOI: 10.1083/jcb.31.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Metaphase Chromosomes From Hela Cells

Abstract: The authors have developed a method for large-scale isolation of metaphase chromosomes from HeLa cells. The distinguishing feature of this method is the use of a pH sufficiently low (about 3) to stabilize the chromosomes against mechanical damage. Many milligrams of fairly pure, morphologically intact chromosomes can be isolated in 8 hr or less of total working time. The isolated chromosomes contain about 2.0 mg of acid-soluble protein, 2.7 mg of acid-insoluble protein and 0.66 mg of R N A for each milligram o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

1968
1968
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…It is likely that histories play a structural role and involved in the coiling of DNA into the compact form of the chromosome (Cole 1962;Richards and Pardon, 1970;Luie and Dixon 1973). According to Huberman and Attardi (1966), human chromosomes include about twice as much proteins at metaphase as at interphase. It seems likely that such increased proteins which consist of both histones and non-histon proteins play a role on maintenance of a chromosomal configuration at metaphase.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that histories play a structural role and involved in the coiling of DNA into the compact form of the chromosome (Cole 1962;Richards and Pardon, 1970;Luie and Dixon 1973). According to Huberman and Attardi (1966), human chromosomes include about twice as much proteins at metaphase as at interphase. It seems likely that such increased proteins which consist of both histones and non-histon proteins play a role on maintenance of a chromosomal configuration at metaphase.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the isolated chromosomes with excellent preservation of morphology and biological activities are very useful materials for studying the fine structure and physico-chemical properties of chromosomes (see Salzman et al 1966;Cantor and Hearst 1966;Huberman and Attardi 1966;Schildkraut 1967, 1969;Mendelsohn et al 1968;Wray and Stubblefield 1970).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many investigators have reported the isolation of metaphase chromosomes from mouse ascites tumor (Cantor and Hearst 1966), mouse lymphocytic leukemia cells (Chorazy et al 1963) and cultured mammalian cells (Somers et al 1963;Huberman and Attardi 1966;Maio and Schildkraut 1966;Salzman et al 1966;Burkholder and Mukherjee 1970). Isolated metaphase chromosomes with excellent preservation of morphology and biological activities are very useful for analyzing the fine structure and physico-chemical properties of chromosomes.…”
mentioning
confidence: 99%
“…Vacuum-dried bovine serum albumin was used as the standard. RNA was determined by the modification of the Schmidt and Thannhauser procedure used by Huberman and Attardi (9). The concentration of the standard RNA solution was determined spectrophotometrically.…”
Section: Chemical Analysismentioning
confidence: 99%
“…For DNA measurements, the suspension was pelleted, and the residue was washed with ethanol-ether (3:1). This residue was well suspended in 0.5 M HC10 4 (9). DNA and RNA were determined as described for the gland analyses.…”
Section: Chemical Analysismentioning
confidence: 99%